2018
DOI: 10.3390/molecules23102627
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico Prediction and Modeling of the Quorum Sensing LuxS Protein and Inhibition of AI-2 Biosynthesis in Aeromonas hydrophila

Abstract: luxS is conserved in several bacterial species, including A. hydrophila, which causes infections in prawn, fish, and shrimp, and is consequently a great risk to the aquaculture industry and public health. luxS plays a critical role in the biosynthesis of the autoinducer-2 (AI-2), which performs wide-ranging functions in bacterial communication, and especially in quorum sensing (QS). The prediction of a 3D structure of the QS-associated LuxS protein is thus essential to better understand and control A. hydrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…These results suggested that the luxS gene promoted AI-2 production and that the luxS gene deletion led to an inability to synthesize AI-2. A LuxS/AI-2 system was reported to exist in C. jejuni, Aeromonas hydrophila (A. hydrophila), E. coli, Actinobacillus pleuropneumoniae (A. pleuropneumoniae), Lactobacillus paraplantarum, A. actinomycetemcomitans, S. pneumoniae, and H. parasuis, etc., and LuxS inactivation affected the growth and/or virulence of the above-mentioned strains (2,3,8,18,21,22,25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that the luxS gene promoted AI-2 production and that the luxS gene deletion led to an inability to synthesize AI-2. A LuxS/AI-2 system was reported to exist in C. jejuni, Aeromonas hydrophila (A. hydrophila), E. coli, Actinobacillus pleuropneumoniae (A. pleuropneumoniae), Lactobacillus paraplantarum, A. actinomycetemcomitans, S. pneumoniae, and H. parasuis, etc., and LuxS inactivation affected the growth and/or virulence of the above-mentioned strains (2,3,8,18,21,22,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the luxS gene could enhance the biofilm formation ability and that the product of the luxS gene could secrete outside the cell and could enhance biofilm formation ability, too. A similar study reported that inhibition of luxS gene expression could inhibit biofilm in E. coli and A. hydrophila (25,37). It is well known that bacterial biofilms increase cell survival through the improved defense of the immune system, increased availability of nutrients, resistance to antibiotics, and better opportunities for cellular communication and transfer of genetic material.…”
Section: Figmentioning
confidence: 91%
“…In a study by Mohammadzadeh et al, after protein modeling of three TA systems and prediction their interaction in Listeria monocytogenes, they designed in silico-derived peptides to inhibit TA systems and the proteins involved in formation persister cells [17]. In another study, considering the importance of LuxS protein in the biosynthesis of autoinducer-2, which plays a significant role in bacterial communication and in particular in the induction of quorum sensing, in silico prediction and modeling of the LuxS in Aeromonas hydrophila was performed and then, the suitable inhibitor for inhibition of AI-2 was identified [39]. These studies provide new knowledge for developing novel therapeutic strategies against bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Most pqs-inhibitors have been identified via costly and timeconsuming biosensor-based screenings or via the rational design and experimental validation of AQ analogs or precursors based on the structure of PqsR and of AQ biosynthetic enzymes. Virtual screenings could reduce the time and costs associated to conventional drug discovery programs, hence in silico techniques have been extensively applied for the identification of molecules hampering the las QS system of P. aeruginosa (Yang et al, 2009;Skovstrup et al, 2013;Tan et al, 2013;Soheili et al, 2015;Gökalsın et al, 2017;Kalia et al, 2017;Xu et al, 2017) or QS systems in other bacteria (Zhu et al, 2012;Ali et al, 2018;Ding et al, 2018Ding et al, , 2019Medarametla et al, 2018). To the best of our knowledge, only synthetic quinoline-based molecules have so far been identified as PqsR antagonists by means of in silico docking analyses (Soukarieh et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%